Mechanical stability of SIS100 Bypass Line busbars clamping system under AC current load. Issue 1 (1st May 2022) - Iluk, A; Chorowski, M; Poliński, J; Eisel, T; Streicher, B; Trockel, R; Grzegory, P
Abstract: This paper presents the lessons learned from tests of first module of superconducting cryogenic bypass line (BPL), a part of the international Facility for Antiproton and Ion Research (FAIR) SIS100 cryogenic system, currently under construction in Darmstadt, Germany. Design, manufacturing, and installation of the superconducting cryogenic bypass line is a part of a Polish in-kind contribution to the FAIR project, realized by the Wroclaw University of Science and Technology. The main goal of the tests was to check the superconducting, Nuclotron type busbar system containing four pairs of busbars, transferring 13.2 kA pulsing current with the ramp rate of 28 kA/s. The mechanical stability of the busbars, especially at the connection region, was investigated with the use of vibration sensors and cameras located inside the vacuum space. The tests revealed insufficient mechanical stability of the busbars in the connection area due to pulsing Lorentz forces, and necessity of additional supports and clamps. Results of the tests were presented and discussed. The conclusions can be significant not only for the bypass line design, but also for design of the busbar connections in the superconducting magnets.